THE ROLE OF SMARTWATCH USAGE IN ENHANCING HEALTH AWARENESS AND TRUST IN DAILY ACTIVITY REMINDER FUNCTIONS - Daffa Risq Mudhoffar Daffa Risq Mudhoffar; Jaka Nugraha Jaka Nugraha; Fatimah Zahra Ouariach Fatimah Zahra Ouariach; Soufiane Ouariach Soufiane Ouariach (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issues: Modern office administration increasingly relies on digital tools to enhance task management. Smartwatches provide real- time reminders that support productivity. Generation Z shows growing interest, but their acceptance of this technology in office contexts is still rarely studied. Purpose: The study aims to analyze the influence of health awareness and trust on smartwatch usage, specifically regarding reminder features used in administrative activities. The research applies the Technology Acceptance Model to understand how these factors affect. Novelty: This study offers novelty by focusing on Generation Z in Surabaya, Indonesia, a group rarely examined in smartwatch adoption research. Previous studies mostly explored millennials or seniors in developed countries. This research highlights how smartwatches support both health awareness and trust in the context of administrative tasks. Research Method: The research uses a quantitative method with convenience sampling. Respondent total of 50 Generation Z respondents from Surabaya, including students and office workers who use smartwatches, participated in the survey. Data were analyzed using variance-based Structural Equation Modeling (SEM). Result: Trust significantly influences perceived usefulness and ease of use, while health awareness does not affect either. Perceived usefulness affects behavioral intention, but ease of use does not. These results indicate that Generation Z users are more likely to use smartwatch features and beneficial for productivity. Research Contributions: The study offers practical insights for office administration by showing that smartwatch usage improves time discipline, task tracking, and user productivity. The findings support the integration of wearable technologies in administrative education